2022
DOI: 10.1007/s00417-022-05940-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of patients with epiretinal membrane-Foveoschisis

Abstract: Purpose The purpose of this study is to investigate the clinical and morphological characteristics of epiretinal membrane (ERM)-Foveoschisis. Methods Medical charts of 2088 patients diagnosed with idiopathic ERM were screened and eyes with ERM-Foveoschisis were included. All eyes underwent a complete ophthalmological examination including spectral domain optical coherence tomography (SD-OCT). OCT features and best corrected visual acuity (BCVA) were analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 27 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…In our study, we found that the patients in group A whose retinal schisis crossing the central fovea might have a better baseline BCVA, a thicker central foveal point thickness, a more complete EZ layer, and better surgical outcomes than those with FS not crossing the foveal center. However, Hetzel et al [13] divided the eyes with ERM-FS into the "closed" and "open" groups according to their OCT images that were similar to our classification, and found that eyes in the "closed" group had a significantly worse BCVA than that in the "open" group. The major reason for the discrepancy may be due to the different severity of disease conditions between the two studies.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…In our study, we found that the patients in group A whose retinal schisis crossing the central fovea might have a better baseline BCVA, a thicker central foveal point thickness, a more complete EZ layer, and better surgical outcomes than those with FS not crossing the foveal center. However, Hetzel et al [13] divided the eyes with ERM-FS into the "closed" and "open" groups according to their OCT images that were similar to our classification, and found that eyes in the "closed" group had a significantly worse BCVA than that in the "open" group. The major reason for the discrepancy may be due to the different severity of disease conditions between the two studies.…”
Section: Discussionsupporting
confidence: 70%
“…The major reason for the discrepancy may be due to the different severity of disease conditions between the two studies. In the cases reported by Hetzel et al [13], not all needed surgical treatment, and the mean initial BCVA was better than that in our study. Because there are few researches on ERM-FS at present, the exact reason for this difference is not clear.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…ERM foveoschisis was previously referred to as a “tractional type of LMH” to distinguish it from a “degenerative LMH” [ 2 , 3 , 4 , 5 , 6 ], although other names have been used [ 7 , 8 , 9 ]. Recently, several studies have reported on the clinical features [ 10 , 11 , 12 ] and postoperative changes in eyes with ERM foveoschisis [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%